ECG Quiz 71 - Chin, A; Millar, RS (SA Heart Journal, 2026)
A 68-year-old man has an electrocardiogram (ECG) performed in the emergency room for an acute episode of palpitations. The patient received an oral antiarrhythmic drug before this ECG.